Collaboration – Building Block and Stumbling Block in Teaching of Information and Reading Literacy: Perceptions of Academic and School Librarians - Fras Popović, Sabina; Vilar, Polona (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
Collaboration between librarians and teachers within formal education, in teaching various literacies has long been recognized as one of the most effective ways of teaching. The paper analyses, using data from three studies, aspects of collaboration between librarians and teachers at primary, secondary and tertiary level. Three research questions focus on forms and extent of collaboration, its elements and approaches, and challenges and obstacles. Results point to still existing differences between higher education and lower levels of education, and to large differences between librarians and teachers in their behaviours, values, attitudes and practices. This opens an important debate around how to effectively approach these issues to improve collaboration, and which of the issues belong to the personal, institutional, and national level. The paper provides some suggestions on how to address these issues at all three levels.